Co-Expression of T- and B-Cell Markers in a Canine Intestinal Lymphoma: A Case Report - Pâmela Cristina Lopes Gurgel Valente; Maria Conceição Peleteiro; Sandra Carvalho; Rodolfo Oliveira Leal; Constança Pomba; António Duarte; Jorge Correia (Animals, 2022)
An 8-year-old female neutered Labrador retriever was presented for a second opinion consultation due to vomiting and lethargy, having failed to respond to symptomatic therapy. Blood analysis revealed hyperbilirubinemia and hypoalbuminemia, associated with hypocobalaminemia. An abdominal ultrasound identified diffused bowel thickening and hypoechoic hepatomegaly. An ultrasound-guided liver fine-needle aspiration was performed for cytology and also for cell block immunocytochemistry. Gastric and duodenal biopsies were collected by gastroduodenoscopy. Liver cytology showed numerous lymphocytes, suggesting lymphoma at the hepatic infiltration stage, and immunocytochemistry in the cell block of the hepatic aspirate indicated co-expression of CD3 and CD20 in the lymphoid cells present. The histopathology of gastric and duodenal biopsies supported the hypothesis of gastrointestinal lymphoma due to heavy lymphoid infiltration of the gastric epithelium and intestinal mucosa, including the villi. Concurrent immunohistochemistry was performed using CD3, CD20, PAX5, and CD79αcy antibodies. Immunomarking was positive for CD3 and CD20, which overlapped populations of lymphoid cells, and was negative for all other antibodies. In the clonality test, lymphocyte co-expression of CD3 and CD20 was confirmed by monoclonal rearrangement of T-cell gamma receptors. The final diagnosis was type 2 enteropathy-associated T-cell lymphoma with hepatic infiltration. Co-expression was examined in conjunction with the PARR result in the presence of T-cell monoclonal rearrangement.